ANALISIS KELAYAKAN FINANSIAL AGROINDUSTRI TAHU (Agroindustri Tahu Bapak Iwan di Desa Pangkalan Pisang Kecamatan Koto Gasib Kabupaten Siak Sri Indrapura) - Riska Dewi; Yusmini '; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research are to know and to analyse the financial feasibility and sensitivity rate of Mr. Iwan’s tahu agroindustry in Pangkalan Pisang Village Koto Gasib District Siak Sri Indrapura Regency. This research used case study method and the number of respondent that one businessman agroindustry. The financial feasibility analysis of tahu agroindustry used investment criterias, such as: Net Present Value (NPV), Net Benefit-Cost Ratio (Net B/C), Internal Rate of Return (IRR), and Payback Period (PP).The result showed that tahu agroindustry business feasible to developed based on its investment criterias, which showed that NPV (positive) was Rp.253.312.974, Net B/C was 3,35 (Net B/C>1), IRR was 52% (IRR>DF 12%), and PP during 4 years 5 months, which means this business has been able to cover the investment cost before the business life ends.Sensitivity analysis can be concluded that soybean prices rise by 10% business is still feasible because NPV (positive), Net B/C>1, IRR>12%, and PP during 7 years 8 months, while when soybean prices rise by 20% business is not feasible because NPV (negative), Net B/C<1, IRR=12%, and PP can not cover the investment cost before the business life ends. Reduction in the scale of production by 10% business is still feasible to proceed because NPV (positive), Net B/C>1, IRR>12%, and PP during 9 years 12 months, while when a decrease in the production scale by 20% business is not feasible because NPV (negative), Net B/C<1, IRR<12%, and PP can not cover the investment cost before the end of business life ends.     Keywords: Agroindustry, Financial Feasibility, Sensitivity, Tahu